2009
DOI: 10.1021/jp901337e
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nanoparticle/Polymer Nanocomposites with Enhanced Photocatalytic Antimicrobial Properties

Abstract: We present a simple method of fabricating highly efficient antibacterial nanocomposite films consisting of a commercially available ethylene−vinyl alcohol copolymer (EVOH) and embedded Ag−TiO2 nanoparticles. These systems display potent antimicrobial activity toward Gram-negative, Gram-positive bacteria/cocci (Escherichia coli 1337-H; Pseudomonas putida KT2440, Staphylococcus aureus 1341-H), and yeasts (Pichia jadini) and, moreover, show outstanding resistance to biofilm formation. These nanocomposites differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 77 publications
1
50
0
Order By: Relevance
“…This striking antimicrobial activity has been also found by using an ethylene-vinyl alcohol copolymer as polymeric matrix [6][7][8]. The existence of energy/charge transfer(s) through these polymer/oxide interfaces and the subsequent development of new electronic states within the nanocomposite system [9] are behind this optimal germicide capability.…”
Section: Introductionmentioning
confidence: 92%
“…This striking antimicrobial activity has been also found by using an ethylene-vinyl alcohol copolymer as polymeric matrix [6][7][8]. The existence of energy/charge transfer(s) through these polymer/oxide interfaces and the subsequent development of new electronic states within the nanocomposite system [9] are behind this optimal germicide capability.…”
Section: Introductionmentioning
confidence: 92%
“…Until now, there have been very few reports that shown to resist biofilm formation on titania based polymer-nanocomposites. In one such study, Kubacka et al [52] have demonstrated photocatalysis using ethylene-vinyl alcohol copolymer (EVOH) embedded with Ag-TiO2 nanoparticles (ca. 10 −2 wt%) that showed outstanding resistance to biofilm formation by bacteria and yeast, upon ultraviolet (UV) light activation.…”
Section: Quantitative Comparisionsmentioning
confidence: 99%
“…Another point of importance to improve the performance of TiO 2 -containing nanocomposite systems concerns the optimization of light absorption and the adequate handling of subsequent charge (electron-hole) pair creation and annihilation processes. This task has been typically attempted by controlling the morphological-structural-defect characteristics of the oxide and/or by extending its absorption power into the visible region through a doping process (Kubacka et al, 2009). Metal doping has long been known to be one of the most effective ways to change the intrinsic band structure of TiO 2 , and consequently, to improve its visible light sensitivity as well as increase its photocatalytic activity under UV irradiation.…”
Section: Polymer Nanocomposites With Enhanced Photocatalytic Antimicrmentioning
confidence: 99%
“…A last point to mention is the concomitant degradation of the polymer matrix by effect of the charge carriers; this has been proved to be limited by addition of small amounts of titania, typically below 5 wt. % (Kubacka et al, 2009). On the other hand high release level of silver, especially for silver based bulk materials, leads to shortening the effective life of antibacterial activity.…”
Section: Polymer Nanocomposites With Enhanced Photocatalytic Antimicrmentioning
confidence: 99%